STUDY OF SEVERE MALNUTRITION IN PRESCHOOL CHILDREN OF MELGHAT - Shelgaonkar, Meena (Indian Journal of Community Health, 2015)
i) Introduction:Melghat - tribal block of villages (with 87.5% tribal population) in Maharashtra, (India) unfortunately is known for malnutrition among children, despite lots of efforts taken by Govt. and NGOs. ii) Rationale: The study was conducted to examine the causes of malnutrition and awareness about consequences of malnutrition as a part of Post-graduate thesis. iii) Objective:Tocompare the status and causes of malnutrition in children below age five in Intervention and Control Villages in Melghat over a period of 2 months. iv) Materials and Methods: A questionnaire based survey method was used by selecting ten villages out of 40 using lottery method where MAHAN, Melghat is already working. Selected ten villages were from Intervention and Control groups (five each). In Intervention villages health and nutritional education awareness programs were conducted while in control group government programs such as 21 day care for severely malnourished children were going on but no health and nutritional education programs. Children’s weight, heights were taken and also general information like mothers educational status was collected in both groups by visiting all families. The data was analyzed for status of malnutrition in preschool children from these families and awareness about nutrition in mothers. v) Results:Status of malnutrition in preschool children was lower in Intervention villages (66.0 %) as compared to that of Control villages (73.0 %), while prevalence was higher among the children whose mothers were illiterate. Malnutrition was higher in girls (70.5 %, 77.1 %) as compared to that of boys (61.4 %, 68.7 %) in both groups. vi) Conclusion: The analysis of study data from tenvillages suggested thatproper health and nutritional education about feeding is lacking in mothers. To reduce this childhood malnutrition proper education and awareness can be used as a major tool along with dietary supplements.